Electrical characterization and modeling of 1T-1R RRAM arrays with amorphous and poly-crystalline HfO2. (February 2017) - Grossi, Alessandro; Zambelli, Cristian; Olivo, Piero; Crespo-Yepes, Alberto; Martin-Martinez, Javier; Rodríguez, Rosana; Nafria, Monserrat; Perez, Eduardo; Wenger, Christian
Abstract: In this work, a comparison between 1T-1R RRAM arrays, manufactured either with amorphous or poly-crystalline Metal–Insulator–Metal cells, is reported in terms of performance, reliability, Set/Reset operations energy requirements, intra-cell and inter-cell variability during 10k endurance cycles and 100k read disturb cycles. The modeling of the 1T-1R RRAM array cells has been performed with two different approaches: (i) a physical model like the Quantum Point Contact (QPC) model was used to find the relationship between the reliability properties observed during the endurance and the read disturb tests with the conductive filament properties; (ii) a compact model to be exploited in circuit simulations tools which models the I – V characteristics of each memory cells technology.